Gently handled foals generalize responses to humans - Schmidek, Anita [UNESP]; De Oliveira, Bruno Nogueira [UNESP]; Trindade, Pedro [UNESP]; Da Costa, Mateus José Rodrigues Paranhos [UNESP] (My University, 2018)
Equines perform tasks along humans, and there are evidences and controversies that they are able to discriminate between familiar and unfamiliar humans. This study assessed whether foals can discriminate between humans in terms of familiarity and human experience in equine handling. Daily, in the first two weeks of life, 30 foals went through a short section of gentle handling. After about four months, a human forced approach test was carried out by 4 evaluators varying in the familiarity aspect and experience with equine handling. Data was submitted to the McNemar test (P<0.05). In 66.7% of the assessments, the foals accepted the human approach, and among the positive cases, 60.0% were characterized by seeking contact with the evaluators. Among the foals that accepted the human approach, 97.5% also accepted tactile stimulation. No differences were found regarding the familiarity of the evaluators (P>0.05) or their experience in equine handling (P>0.05). The individual variation was evident, which indicates that we must work with personalized training techniques, in which the behavior of each individual is the main factor to be considered. Our results show that the adoption of good handling practices with foals favored their relationship with humans, and it is possible to assume that such practices can improve animal welfare, as well as the safety of the humans that will have contact with them in the future.
Keywords: Animal welfare; Equines; Training